FACTORS INFLUENCING STUDENTS’ LISTENING COMPREHENSION AT THE FOURTH SEMESTER ENGLISH STUDY PROGRAM OF UNISI TEMBILAHAN - Mukhdar Mukhdar; Melda Yeni (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2019)
This research was done because the researchers found that most of the students' listening comprehension of the fourth semester was low. Therefore, the researchers decided to conduct research about factors that causing it. So that the researchers want to find out students' listening comprehension factors at English study program of UNISI. This aim was achieved through a descriptive qualitative design. The sample of this research was the students of the fourth semester of English Study Program of UNISI. They consist of 13 students. They were chosen by using total sampling technique. By conducting this research, the researcher found that there are three factors influencing students’ listening comprehension at the fourth semester of English Study Program of UNISI, they are reduced form, colloquial language and rate of the delivery. It can be interpreted that their low result in listening to English monologue text was because of those factors.